Indonesia's Maritime Diplomacy Strategy In The Natuna Sea (2014-2024) - Aji, Muhammad Sajidin; Mu'min, Mu'min (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study examines the maritime diplomacy strategy carried out by Indonesia in maintaining Indonesia's sovereignty in the Natuna Islands. The maritime border in the Natuna Islands is vulnerable even though Indonesia has declared the area around the Exclusive Economic Zone (EEZ) as part of Indonesia's sovereign rights in accordance with the United Nations Convention for the Law of the Sea (UNCLOS). As a result, the waters of Indonesia's Exclusive Economic Zone (EEZ) recognized by UNCLOS are considered Chinese territory in the South China Sea. Qualitative methods with a descriptive approach are used in research to find the meaning and efforts of maritime diplomacy carried out by Indonesia with sources obtained through journals and research. The purpose of this research is to understand the strategy carried out by the Indonesian government in conducting maritime diplomacy in a cooperative, persuasive and coercive manner by taking diplomatic steps while inviting respect for Indonesia's sovereign rights. The result of this study is that Indonesia and China have made various diplomatic efforts to reduce disputes in the South China Sea.